Evaluation of rootstocks for the multiplication of Phaseolus albicarminus Debouck & N. Chaves - Sabogal Carvajal, R; Gereda, J.M; Escobar Guzman, H; Santaella, M; Debouck, Daniel G. (2023)
The wild bean P. albicarminus accession G40901 conserved in the Future Seeds germplasm bank (Palmira, Colombia) is currently not available because of lack of seeds for distribution. This living collection has been noted as susceptible to attacks of nematodes and root rots, putting the accession at risk.